2020
DOI: 10.3390/mi11100926
|View full text |Cite
|
Sign up to set email alerts
|

Surface Characterization and Tribological Performance Analysis of Electric Discharge Machined Duplex Stainless Steel

Abstract: The present article focused on the surface characterization of electric discharge machined duplex stainless steel (DSS-2205) alloy with three variants of electrode material (Graphite, Copper-Tungsten and Tungsten electrodes). Experimentation was executed as per Taguchi L18 orthogonal array to inspect the influence of electric discharge machining (EDM) parameters on the material removal rate and surface roughness. The results revealed that the discharge current (contribution: 45.10%), dielectric medium (contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Electrical discharge machining (EDM) is a modern processing machining method for materials that are difficult to use with conventional methods [1][2][3] as a result of high hardness, high wear resistance, and other special properties [3][4][5][6][7][8][9]. EDM is a machining process that removes some of the work material from the workpiece using the high temperature produced by spark discharges to erode the workpiece [3,8,10].…”
Section: Introductionmentioning
confidence: 99%
“…Electrical discharge machining (EDM) is a modern processing machining method for materials that are difficult to use with conventional methods [1][2][3] as a result of high hardness, high wear resistance, and other special properties [3][4][5][6][7][8][9]. EDM is a machining process that removes some of the work material from the workpiece using the high temperature produced by spark discharges to erode the workpiece [3,8,10].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have mainly focused on low production costs and better EDM performance outputs. The approach for lowering the EDM process cost is basically to choose Cu (or its alloys) as electrode material that possesses low raw material and production costs as well as high MRR and electrical wear resistance (i.e., low TWR and RW) [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…However, some reported work revealed that EDMed DSS-2205 alloy exhibits superior bioactivity as well as corrosion resistance responses compared to the unmachined substrate. 27,28 The present work aimed to investigate three different electrodes, namely graphite, tungsten, and copper-tungsten for the ED machining performance of the Co-Cr alloy and duplex stainless steel. The topographical examination of the machined surfaces was carried out via field emission scanning electron microscopy, whereas compositional studies of the treated samples analyzed using energy-dispersive Xray spectroscopy and X-ray diffraction analysis.…”
Section: Introductionmentioning
confidence: 99%